Autoreactive TCD8+ lymphocytes in patients with chronic myeloid leukemia in association with HLA and adenovirus infection - Sergio E. Rivera-Pirela; Miriam Echeverría; Pedro Salcedo; Georgina Márquez; Zuhey Carrillo; Yennis Parra; Ana María Cipriani; José R. Núñez; Melchor Álvarez de Mon; Atilio Farruco (Revista Alergia México, 2016)
Background: A possible interaction between a specific HLA type and Adenovirus has been postulated as a promoter in leukemia clonal evolution. The HLA-DRB1*14, specifically DRB1*14:21, 14:22, 14:45, 14:26, 14:33, 14:51, 14:35 subtypes was the most frequent in CML venezuelan patients. Objectives: It is interesting to evaluate the molecular mimicry between the Adenovirus and the DRB1*14 subtypes which exhibit the same change in the amino acid position of the DR53 epitope. This mimicked segment has been identified as a LLERRRA polypeptide. Material and methods: Experimental research conducted in the IHO Venezuela, in peripheral blood samples of patients with ALL, CML and healthy controls. Mixed culture, serology, lymphocyte proliferation and cytofluorometry were performed. Results: DRB1*14 patient’s lymphocytes reacted in 48 hours mixed culture against DRB1*14 promoters lymphocytes exhibiting increased CD8+T lymphocytes. CML patients show a different serological profile against Adenovirus. Only CML patients reacted to LLERRRA peptide, increasing CD8+ T cells. Conclusion: It is established that the relationship CML, HLA-DRB1*14, autoreactive CD8+ T memory cell and CD8+T specific response from Adenovirus could be at the origin of the CML in venezuelan.